Analisis Kekuatan Jembatan Konstruksi Baja Sungai Merangin Teluk Wang - M Nuklirullah; Erwin Siregar (Universitas Batanghari, 2018)
Merangin Regency has many natural beauty and has various tourist attractions. One of them is Wang waterfall which is located in Biuku Tanjung village. To get to the object, once visitors must cross the river by boat. But now the government has built a pedestrian bridge with a span 48 meters to the waterfall tourist attractions, making it easier for visitors. Every year the visitors are growing. The purpose of this study is to analyze the strength of the bridge that is in the tourist attraction. Load and Resistance Factor Design (LRFD) method used in analyzing bridges with 2 dimensional structure modeling in the form of portal structure. The data in this research is primary data obtained with direct observation and measurement of field and secondary data is drwing plan of bridge. From the results of structural calculation analysis, all of the planned dimensions meet the strength and security requirements of the structure.Key words : Steel Structure, pedestrian bridge, LRFD method